Hubungan Tingkat Pengetahuan Masyarakat tentang COVID-19 dengan Perilaku Penerapan Protokol Kesehatan Era New Normal di Wilayah Puskesmas Kartasura Kabupaten Sukoharjo - 'Aisyah Nilam Cahyani; Anjar Nurrohmah (Indonesian Journal on Medical Science, 2023)
Corona Virus Disease (COVID-19) is an infectious disease caused by the coronavirus group, where this disease has spread rapidly throughout the world, including Indonesia. The Kartasura sub-district is the first-ranked area with the most COVID-19 cases in Sukoharjo Regency. The government and authorities continue to urge the public not to ignore the dangers of COVID-19 and the importance of implementing health protocols. Good community behavior in implementing health protocols is influenced by the knowledge factor. The purpose of this study was to analyze the relationship between the level of public knowledge about COVID-19 and the behavior of implementing health protocols in the New Normal era in the Kartasura Health Center area. This study used an analytic observation method with a cross sectional design. Sampling using non-probability sampling method with a total sample of 97 respondents. The results showed that the results of the Spearmen Rank test were between the Level of Public Knowledge about COVID-19 and the Behavior of the Implementation of the New Normal Era of Health Protocols in the Kartasura Health Center area, Sukoharjo Regency (p value = 0.024). There is a significant relationship between the level of public knowledge about COVID-19 and the behavior of implementing the New Normal Era of Health Protocols in the Kartasura Health Center area, Sukoharjo Regency.Corona Virus Disease (COVID-19) is an infectious disease caused by the coronavirus group, where this disease has spread rapidly throughout the world, including Indonesia. The Kartasura sub-district is the first-ranked area with the most COVID-19 cases in Sukoharjo Regency. The government and authorities continue to urge the public not to ignore the dangers of COVID-19 and the importance of implementing health protocols. Good community behavior in implementing health protocols is influenced by the knowledge factor. The purpose of this study was to analyze the relationship between the level of public knowledge about COVID-19 and the behavior of implementing health protocols in the New Normal era in the Kartasura Health Center area. This study used an analytic observation method with a cross sectional design. Sampling using non-probability sampling method with a total sample of 97 respondents. The results showed that the results of the Spearmen Rank test were between the Level of Public Knowledge about COVID-19 and the Behavior of the Implementation of the New Normal Era of Health Protocols in the Kartasura Health Center area, Sukoharjo Regency (p value = 0.024). There is a significant relationship between the level of public knowledge about COVID-19 and the behavior of implementing the New Normal Era of Health Protocols in the Kartasura Health Center area, Sukoharjo Regency.